Incorporating personal narratives in positive psychology interventions to manage chronic pain - Georgiadis, Emmanouil; Johnson, Mark I. (Frontiers in Pain Research, 2023)
In this perspective paper, we argue for incorporating personal narratives in positive psychology interventions for chronic pain. Narratives refer to the telling and retelling of events. Narratives detail accounts of events and provide rich, in-depth information on human interactions, relationships, and perspectives. As such, narratives have been used to understand people’s experiences with pain and pain coping mechanisms—as well as to facilitate therapeutic outcomes. Furthermore, narrative research has shown that narration can help restore and promote relief, calm, hope, self-awareness, and self-understanding in chronic pain sufferers. Positive psychology interventions have been successful in improving the lives of people living with chronic pain, but these psychology interventions do not typically incorporate personal narratives. Still, narrative, and positive psychology scholarship foci overlap, as both aim to enhance people’s quality of life, happiness, and well-being, and to promote the understanding of psychosocial strengths and resources. In this article, we provide a rationale for incorporating personal narratives as an agentic form of positive psychology intervention. To that aim, we outline areas of convergence between positive psychology and narrative research and show how combining positive psychology exercises and narration can have additive benefits for pain sufferers. We also show how integrating narration in positive psychology intervention research can have advantages for healthcare research and policy.